Selective serotonin reuptake inhibitor associated suicidal ideation: a case report - Mukherjee, Shatavisa; Sen, Sukanta; Ghosal, Malay Kumar; Tripathi, Santanu Kumar (International Journal of Basic & Clinical Pharmacology, 2017)
This report describes a patient suffering from somatoform disorder that developed suicidal ideation specifically due to the treatment with sertraline. After 6-7 months on the regimen, she presented slight suicidal ideations. However, with gradual progress of time and continuation of the therapy, the ideation became intense. She complained of intense restlessness and anxiety. She presented with fresh cuts and bruises on her left arm and neck. On reporting the problem, the drug was withdrawn. Patient experienced gradual improvement in her state. The case report underlines the importance of onset of suicide risk in panic disorders due to specific antidepressants, selective serotonin reuptake inhibitors (SSRIs). The exact neurobiological basis of depression though being uncertain, the role of serotonin has been mostly implicated. Hypothetically, biological alterations in the serotonergic system might have contributed to the suicidal ideation/attempt in the presence of an SSRI. The present case attempts to highlight an incidence of development of suicidal ideation in a patient who is on chronic SSRI therapy.